2018
DOI: 10.1177/0091450918777280
|View full text |Cite
|
Sign up to set email alerts
|

“I Lost Me Visits”

Abstract: Utilizing Bacchi's poststructuralist approach, "What's the problem represented to be?," we critically examine how the "problem" of drug use in prison is represented within a key initiative-the Identified Drug User program (IDUP)-of prison drug policy in one Australian jurisdiction. We use two data sources for our analysis: interview transcripts of recently incarcerated young men (aged 19-24) with histories of injecting drug use and selected prison drug policy and program documents. We examine how the "problem"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 106 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…Taken together, our findings suggest that there are few opportunities to receive backup and input from family and friends that support the goals of the treatment (motivation to seek change and enter voluntary treatment), given the current situation at the studied institutions. Prior research has shown that efforts to maintain relationships with family, primarily through visits during incarceration, are associated with better post-release outcomes (Berg & Huebner, 2011;Eades, 2009;Taylor, 2016;Walker et al, 2018). We argue that opportunities for improvement may lie in a higher degree of permeability within compulsory treatment settings.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Taken together, our findings suggest that there are few opportunities to receive backup and input from family and friends that support the goals of the treatment (motivation to seek change and enter voluntary treatment), given the current situation at the studied institutions. Prior research has shown that efforts to maintain relationships with family, primarily through visits during incarceration, are associated with better post-release outcomes (Berg & Huebner, 2011;Eades, 2009;Taylor, 2016;Walker et al, 2018). We argue that opportunities for improvement may lie in a higher degree of permeability within compulsory treatment settings.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, when it comes to detainment of people in a Swedish compulsory treatment setting, the prison functions as a point of reference. A large body of prison research has shown the importance of maintaining family bonds while incarcerated, for a more positive post-release outcome (e.g., Berg & Huebner, 2011;Walker et al, 2018). While few studies focus on relationships outside of the family, they point out the importance of inmates keeping contact with the outside world while detained, for a more successful reentry into society (Eades, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is how governing takes place, how governmental practices contribute to the production of subjects, and how these have implications on people's lived experience (Bacchi, 2009(Bacchi, , 2017Bacchi & Goodwin, 2016). Although predominantly used as a tool for interrogating text in the form of policy and legal documents (see Bacchi, 2009Bacchi, , 2015Bacchi, , 2017Lancaster et al, 2015;Moore & Fraser, 2013;Seear & Fraser, 2014;Walker, Lancaster, et al, 2018), WPR has increasingly been used to reflect critically on problematizations that are not strictly textual, such as buildings, artifacts, and other phenomena (see Arousell et al, 2017;Bacchi & Goodwin, 2016;Bonham & Bacchi, 2017;Bottrell & Goodwin, 2011). Our analysis builds on these studies, using the carceral space of police custody as the site of problematization.…”
Section: Theoretical Framework and Methodsmentioning
confidence: 99%
“…Interview data are drawn from a doctoral dissertation study about the experiences of drug use, incarceration, and release from adult prison for 28 young men with histories of injecting drug use Walker, Lancaster, et al, 2018;Walker, Seear, et al, 2019). Young men were recruited via the Prison and Transition Health (PATH) longitudinal cohort study, involving 400 male prisoners who reported injecting drugs at least monthly for the 6 months prior to their most recent incarceration.…”
Section: Qualitative Interview Datamentioning
confidence: 99%